Framing super typhoon Haiyan by Philippine and international online news sites - Canubas, Aletheia G.; Barroga-Jamias, Serlie; Tirol, Ma. Stella C. (2016)
This qualitative study used Framing Theory to surface the themes and rhetoric building toward frames used in the reportage of two local online news (bulatlat.com and Interaksyon.com) websites about Typhoon Haiyan, the so-called "deadliest natural disaster" that hit the Philippines in 2013 and killed more than 6,000 people. A total of 654 articles published from November 2013 to November 2014, covering the pre-, during-, and after-landfall phases of the typhoon, were analyzed.

Results showed that both local and international stories worked around the frames of reponsibility, humanitarian aid, destruction, damage, and death/crisis, and hybrid of hegemonic and human drama/interest. The difference lies in the themes and rhetoric under each frame used in the year long reportage. The 'disaster awareness/warning' frame used in the pre-landfill phase was a necessary frame in that specific timeline. However, the general tone of the articles in this frame was that 'everything is ok', which proved fatal when Typhoon Haiyan made landfall. The 'responsibility' frame was th primary focus of the coverage from all the phases and by both local and international news sites. Local media highlighted the complexities of the shortcomings of the government in its response to the various aspects of disaster relief as shown at various time frames. Reports tried to make sense of the devastation by looking at who was to blame, or what could have been done, and what must be done next. In the end, it is still the local and not the international media that must sustain reportage throughout the post-disaster rehabilitation.